PERAN KURIKULUM MERDEKA TERHADAP SEMANGAT BELAJAR PENDIDIKAN AGAMA ISLAM SISWA SMA NU KEJAJAR, WONOSOBO - Yulia Uswatun Hasanah; Abdul Majid; Fatiatun Fatiatun (Al-Mau'izhoh, 2023)
The Independent Curriculum is one of the new curricula implemented in the new school year, namely 2022.  Curriculum changes in Indonesia are very fast, causing many shortcomings in education, one of which is at SMA NU Kejajar Wonosobo which has implemented the Independent Curriculum in the new learning year 2022. Researchers took the place of research at SMA NU Kejajar with the aim of knowing the role of the Independent Curriculum on the spirit of learning Islamic Religious Education of NU Kejajar High School students, and to find out the supporting and inhibiting factors of learning Islamic Religious Education at SMA NU Kejajar. Researchers use qualitative field research methods, research is carried out at the research site by means of observation, interviews and documentation.  The results of the research on the Role of the Independent Curriculum on the Spirit of Learning Islamic Education for NU Kejajar High School students are, the Curriculum is able to provide an active role in the learning and assessment of Islamic Religious Education for NU Kejajar High School students, the supporting factor of the Independent Curriculum is the enthusiasm of students to learn Islamic Religious Education which is high and supported by male and female dormitories for recitation,  while the inhibiting factor is teachers who have not understood the changes in the Independent Curriculum in schools, resulting in independent learning becoming learning for mere assessment.